EFFORTS OF TAHFIZH AL-QURAN TEACHERS TO IMPROVE THE ABILITY OF STUDENTS TO MEMORIZE AL-QURAN - Latifah; Syofrianisda (Amanah Publishing, 2025)
The purpose of this study was to determine the efforts of Quran memorization teachers in improving the Quran memorization skills of students at Cahaya Makkah Islamic Junior High School in West Pasaman Regency. This study used a qualitative research method with a descriptive approach. Data were collected through interviews, observation, and documentation. The results of this study indicate that the efforts of Quran memorization teachers in improving the Quran memorization abilities of students at Cahaya Makkah Islamic Junior High School in West Pasaman Regency include: program development, guidance of male and female teachers in Quran memorization, Quran curriculum development, Quran group formation, motivation for students before memorizing the Quran, preparation of memorization control books, Quran muqayyam (introduction to the Quran), monitoring students during the Quran memorization program, ensuring students perform Tahajjud prayers regularly, impressively impressive. on students who do not achieve their targets, rewarding students who have achieved their targets, and conducting evaluations.